Pengaruh Orientasi Etis, Gender, Dan Pengetahuan Kode Etik Akuntan Terhadap Persepsi Mahasiswa Akuntansi Mengenai Perilaku Tidak Etis Akuntan - Ketut Ria Mutiarasari; I Putu Julianto (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of Idealism, Relativism, Gender, and Knowlegde of Ethic Accounting Code of Accounting Students’ Perseption on Unethical Accounting Behavior. This study used quantitative approach with primary data obtained from questionnaires and measured using a Likert Scale. The population of this study were accounting students at five universities in Bali in total 1,115 people. The sampling technique used convenience sampling with a sample criteria of accounting students who had been interned or worked at a Public Accounting Firm or at an Accountant Services Office, and accounting student who had taken courses in the Accounting Professional Education program. Determination of the minimum number of samples used the Isaac and Michael tables with a significance level of 5%, obtained a total sample of 265 people. Data analysis technicque used multiple linear regression analysis by using SPSS 22.0 for Windows. The result showed that idealism and knowledge of ethic accountant code had a negative influence on accounting student’ perseptions of accountant’s unethical behavior, while relativism had positive influence on accounting students’perseptions of accountant’s unethical behavior and male accounting students’ perception was proven more support unethical accountant’s behavior rather than female accounting students.